Pre-exercise hyperhydration interventions in adult endurance athletes: a systematic review of performance, physiological, and tolerability outcomes - Zahar, Ammar; Sazali, Razif; Md Yusoff, Yusandra; Zulqarnain, Muhammad; Haziq, Amrun; Adnan, Aizzat; Linoby, Adam (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This systematic review, registered with PROSPERO and following PRISMA guidelines, critically evaluates the impact of pre-exercise oral hyperhydration on endurance performance and physiological responses in healthy adults. By searching major databases through January 2025, the study synthesized randomized and non-randomized trials to assess primary outcomes like time-trial results and secondary measures including plasma volume, thermoregulation, and gastrointestinal tolerability. The analysis aims to address inconsistent evidence caused by methodological heterogeneity and gaps in sex representation, providing clearer mechanistic insights for athletic hydration strategies.